2022
DOI: 10.1007/s10709-022-00158-6
|View full text |Cite
|
Sign up to set email alerts
|

Solving the grand challenge of phenotypic integration: allometry across scales

Abstract: Phenotypic integration is a concept related to the cascade of trait relationships from the lowest organizational levels, i.e. genes, to the highest, i.e. whole-organism traits. However, the cause-and-effect linkages between traits are notoriously difficult to determine. In particular, we still lack a mathematical framework to model the relationships involved in the integration of phenotypic traits. Here, we argue that allometric models developed in ecology offer testable mathematical equations of trait relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…For example, a reduction in specific leaf area (SLA) is usually coupled with an increase in leaf dry matter content (LDMC; Wright et al ., 2004). Under this premise, traits vary in a coordinated way to optimize some functions at the cost of others (Messier et al ., 2017; Vasseur et al ., 2022). As a result, it is suggested that phenotypic integration (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a reduction in specific leaf area (SLA) is usually coupled with an increase in leaf dry matter content (LDMC; Wright et al ., 2004). Under this premise, traits vary in a coordinated way to optimize some functions at the cost of others (Messier et al ., 2017; Vasseur et al ., 2022). As a result, it is suggested that phenotypic integration (i.e.…”
Section: Introductionmentioning
confidence: 99%